(untitled) (Eurasian Journal of Medical and Natural Sciences, 2026)
The present study addresses the clinically significant issue of anal intraepithelial neoplasia (AIN) in women with previously diagnosed human papillomavirus (HPV)-associated lesions of the cervix, vulva, and vagina. Particular emphasis is placed on the role of the anal canal as a potential viral reservoir, facilitating persistent HPV infection. The concept of “field cancerization” is considered as a theoretical framework explaining the high prevalence of multifocal lesions within the anogenital epithelium.